"Drop the Body": Body Disposal Patterns in Sexual Homicide. (May 2021) - Chai, April Miin Miin; Beauregard, Eric; Chopin, Julien
The current study investigates body disposal patterns in sexual homicide and examines whether offender's behavior differ between solved and unsolved cases. To address these two research questions in line with rational choice perspective, a series of logistic regression analyses was conducted on a sample of 250 solved, and 100 unsolved sexual homicide cases in Canada. Within solved cases, results show that if victim is a prostitute, body found concealed, and found lying face down, it is likely the body was moved. For unsolved cases, the role of victim as a prostitute, and body recovered outdoors suggest that the body was moved. Further, results indicate that post-crime phase factors predicted the most whether the victim's body was moved in solved cases. Whereas within unsolved cases, crime-phase factors contributed the most at predicting whether the body was moved post-homicide. Theoretical and practical implications from this study are discussed.